Inhibition of uroporphyrinogen decarboxylase by halogenated biphenyls in chick hepatocyte cultures. Essential role for induction of cytochrome P-448. - Sinclair, P R (1984)
Uroporphyrinogen decarboxylase (EC 4.1.1.37) activity was assayed in cultures of chick-embryo hepatocytes by the changes in composition of porphyrins accumulated after addition of excess 5-aminolaevulinate. Control cells accumulated mainly protoporphyrin, whereas cells treated with 3,4,3',4'-tetrachlorobiphenyl or 2,4,5,3',4'-pentabromobiphenyl accumulated mainly uroporphyrin, indicating decreased activity of the decarboxylase. 3-Methylcholanthrene and other polycyclic-hydrocarbon inducers of the P-448 isoenzyme of cytochrome P-450, did not affect the decarboxylase in the absence of the biphenyls. Induction of P-448 was detected as an increase in ethoxyresorufin de-ethylase activity. Pretreatment of cells with methylcholanthrene decreased the time required for the halogenated biphenyls to inhibit the decarboxylase. The dose response of methylcholanthrene showed that less than 40% of the maximal induction of cytochrome P-448 was needed to produce the maximum biphenyl-mediated inhibition of the decarboxylase. In contrast, induction of the cytochrome P-450 isoenzyme by propylisopropylacetamide had no effect on the biphenyl-mediated decrease in decarboxylase activity. Use of inhibitors of the P-450 and P-448 isoenzymes (SKF-525A, piperonyl butoxide and ellipticine) supported the concept that only the P-448 isoenzyme is involved in the inhibition of the decarboxylase by the halogenated biphenyls. The effect of preinduction with methylcholanthrene to enhance inhibition of the decarboxylase was also shown by the increased rate at which porphyrin accumulated from endogenously synthesized 5-aminolaevulinate after treatment of cells with the combination of propylisopropylacetamide and the biphenyls. Antioxidants, chelators of iron, and chromate affected the decrease in decarboxylase activity only if they prevented the induced increase in cytochrome P-448. We conclude that the P-448 and not the P-450 isoenzyme of cytochrome P-450 plays an obligatory role in the inhibition of uroporphyrinogen decarboxylase caused by halogenated biphenyls.